Pelaksanaan Pembelajaran Pendidikan Sistem Ganda di Lembaga Pasangan Sekolah Menengah Kejuruan - Sutrisno Sutrisno; Peryono Peryono (Universitas Negeri Malang, 2016)
The purpose of this study was to describe the dual system of education implemented by vocational secondary schools (SMK) and their counterparts, especially in student selection, instructional process, evaluation, and the student's and instructor's readliness. The sample consisted of 68 SMK students from 17 departments of SMK and 34 instructors from 17 industrial institutions in Malang Municipality. Data were collected by administering a questionnaire. The results revealed that there was no selection applied to recruit the SMK students. The delivery system, training materials, evaluation of student's performance, and the student's and instructor's readliness were good enough, but the training facilities were inadequate